2017
DOI: 10.7324/jabb.2017.50108
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella pneumoniae VRE36 as a PGPR isolated from Saccharum officinarum cultivar Co99004

Abstract: Klebsiella species known to exhibit important PGP traits like solubilization of phosphate, phytohormone production and good germination potential. In present study, based on the Phosphate solubilization and IAA production bacterial strain VRE36 was selected among the isolates collected from different sugarcane cultivar rhizosphere growing near Bardoli area for characterization and molecular identification through 16S rRNA gene sequence, which confirms the isolate as Klebsiella pneumoniae. The phosphate solubil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 18 publications
(19 reference statements)
5
32
0
1
Order By: Relevance
“…Klebsiella pneumoniae, a human pathogen, also showed a plant growth promoting characteristic, in a high level producing IAA and solubilizing phosphate. Similar result reported by Bhardwaj, Shah, Joshi, and Patel (2017) that Klebsiella pneumoniae VRE36 associated with sugarcane exhibit important plant growth promoting traits. In soil, most phosphate occur as insoluble form that cannot be absorbed by plants (Rengel and Marschner, 2005).…”
Section: Discussionsupporting
confidence: 88%
“…Klebsiella pneumoniae, a human pathogen, also showed a plant growth promoting characteristic, in a high level producing IAA and solubilizing phosphate. Similar result reported by Bhardwaj, Shah, Joshi, and Patel (2017) that Klebsiella pneumoniae VRE36 associated with sugarcane exhibit important plant growth promoting traits. In soil, most phosphate occur as insoluble form that cannot be absorbed by plants (Rengel and Marschner, 2005).…”
Section: Discussionsupporting
confidence: 88%
“…Among all eight isolates F372 (15 mg L -1 ) was found best isolates as phosphate solubilizers followed by ESB4 (14 mg L -1 ) ( Table 5). Similar consistent results of phosphate solubilization in both agar and broth assay were observed earlier [1,23]. Quantification of IAA was carried out for eight different isolates.…”
Section: Isolation and Characterization Of Rhizobacteriasupporting
confidence: 57%
“…Importance of sugar in human diet needs no introduction; it has become a part and parcel of daily life. As sugarcane is a long duration crop and faces many biotic and abiotic stresses during growth phase, the microorganism associated with sugarcane roots may be potent and useful for application to promote plant growth [1]. Soil microorganisms play a significant role in regulating the dynamics of organic matter, decomposition and the availability of plant nutrients such as Nitrogen (N), Phosphorous (P) and Sulfur (S).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, AWD5 has pqqBCDEF locus, which directed the synthesis of PQQ, a co-factor of glucose dehydrogenase holoenzyme (GDH) (Meulenberg et al 1992 ). Bhardwaj et al ( 2017 ) reported that K. pneumoniae VRE36 produced 45 µg/ml of IAA and estimated 17.4 µg/ml release of available phosphate in NBRIP medium.…”
Section: Discussionmentioning
confidence: 99%
“…It had been reported that K. pneumoniae strains were found to enhance the plant growth, seed germination rate in maize, wheat, sugarcane, etc. (Sachdev et al 2009 ; Kuan et al 2016 ; Bhardwaj et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%